Design and Development of a Date Harvesting Machine - Shamsi, Mohsen (Cranfield University, 1998)
Existing date harvesting machines are vehicles equipped with a long arm to lift a man on a platform to harvest the fruits. The arm and the vehicle are heavy (4 to 8 tonnes), expensive (from £16 000) and are not sufficiently manoeuvrable in constricted date groves. Most dates in the main producing countries, including Iran, are therefore harvested manually. The manual method is unsafe, slow, expensive (£0.63 per tree) and the fruit quality is often damaged. A light, weight 4 wheel drive, remotely controlled tree climbing machine is, therefore, a potential solution to the problems of harvesting and servicing (such as pollinating and pruning). A prototype of such a device was designed, developed and evaluated under laboratory conditions. To determine the operating characteristics and feasibility the machine was designed to climb the tree using pneumatic tyres as traction wheels. The machine can be transformed to ground drive and move between trees under its own power. This approach reduces the machine weight, cost and size because the tree trunk is used as a support for the machine to climb to the fruits. It is operated and controlled from the ground which improves the operator safety. A vertical traction theory for this type of machine has been developed based on the tree size and surface characteristics and machine size and weight which can be used to design date harvesting and climbing machines with different capacities. The test results showed that the experimental machine could achieve a tractive efficiency of 90% and that the optimum wheel slippage was between 10 - 15%. The machine consumes a maximum of 1.4 kW power which is only 3% of the power requirement of existing systems. The machine weight is 150 kg which is 2- 4% of the existing systems' weight. It is capable of climbing the tree at a maximum speed of 0.27 m/s although the optimum speed is 0.17 m/s for best control. The prototype can carry a payload of 100 kg of dates and, considering a field efficiency of 75%, it can potentially harvest a tree in 22 minutes which is 18 % faster than the manual system in Iran and 6% faster than one of the mechanised systems used in Saudi Arabia. The harvester can work on tree diameter ranges from 300 to 850 mm and can pass over the tree leaf bases of 41 mm high. The machine should not damage the tree because the tree resists the machine stresses with a minimum safety factor of 7. An economic analysis showed that it can be manufactured in Iran at 20 % of the cost of existing systems. The machine cost per tree is equal to the hand harvesting method (£O. 63 per tree) for Iranian farmers if it harvests 978 trees per year.